2023
DOI: 10.3389/fphar.2023.1095366
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis as a therapeutic target for inflammation-related intestinal diseases

Abstract: Ferroptosis is an iron-dependent programmed cell death characterized by reactive oxygen species-induced lipid peroxidation and resultant membrane damage. Recent research has elucidated the mechanism of ferroptosis and investigated the relationship between ferroptosis and various diseases, including degenerative diseases, cancer, and inflammation. Ferroptosis is associated with inflammation-related intestinal diseases such as colitis and colitis-associated cancer. New insights into the role of ferroptosis in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…To improve patient quality of life, increase life expectancy, and lessen the burden on society, it is crucial to understand the pathogenesis of NDs and identify effective therapeutic targets. At the same time, a considerable number of studies have shown an association between the onset and progression of NDs and ferroptosis (Gallucci et al 2008 ; Wu et al 2021 ; Zhang et al 2023 ) (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…To improve patient quality of life, increase life expectancy, and lessen the burden on society, it is crucial to understand the pathogenesis of NDs and identify effective therapeutic targets. At the same time, a considerable number of studies have shown an association between the onset and progression of NDs and ferroptosis (Gallucci et al 2008 ; Wu et al 2021 ; Zhang et al 2023 ) (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 92%
“…Nrf2-associated markers of ferroptosis require binding to others for specific detection and detection of cellular ferroptosis. Nevertheless, according to several studies (Habas et al 2013 ), Nrf2 has become an important therapeutic target of NDs because of its important role in protecting neurons from OS and glutamate-induced excitotoxicity and ultimately maintaining the survival of injured neurons (Zhang et al 2023 ).…”
Section: Biomarkers and Therapeutics Targeting Nrf2 And Ferroptosis I...mentioning
confidence: 99%
“…Iron overload has been linked to ferroptosis, an intracellular iron-dependent form of cell death [67,70,71]. This process involves the release of damage-associated molecular patterns (DAMPs) and lipid peroxidation products, which in turn activate the NF-κB pathway, leading to inflammation [72]. Furthermore, iron overload has been correlated with increased levels of vascular endothelial growth factor A (VEGFA) and IL-8, proinflammatory cytokines described above, thus triggering inflammation through an additional mechanism [70,73,74].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Among the different aldehydes that can be formed as secondary products during lipid peroxidation, malondialdehyde and 4-hydroxynonenal (4-HNE) stand out, both being associated with different stages of MAFLD [208]. In turn, arachidonic acid and adrenic acid-containing phosphatidylethanolamines (PEs), vulnerable to ROS attack, are the main substrates for lipid peroxidation; such long-chain polyunsaturated fatty acids are preferentially catalyzed to their acyl-CoA esters by long-chain acyl-CoA synthetase family member 4 (ACSL4), re-acylated into lysophospholipids by lysophosphatylcholine acyltransferase 3 (LPCAT3), and subsequently oxidized by lipoxygenase, resulting in membrane rupture and ferroptotic cell death [209].…”
Section: Ferroptosismentioning
confidence: 99%